Species Diversity, Distribution and Abundance of Fishes of Seti Gandaki River Basin, Pokhara, Nepal - Pokharel, Kishor K.; Basnet, Khadga B.; Majpuria, Trilok C.; Baniya, Chitra B. (Himalayan Biodiversity, 2020)
Species diversity with indices, distribution and abundance of fishes of Seti Gandaki River Basin, Pokhara, Nepal are described from five study sites, three along the main channel and two in major tributaries. Fishes were sampled using a cast-net following pass-removal method. Environmental variables were determined following the standard methods. In total, 30 species belonging to five orders, nine families and 24 genera with absolute abundance of 10,659 were recorded. A longitudinal pattern of distribution and species richness from upstream to downstream sites (17 to 21 species) was observed. Cyprinids were dominant followed by silurids, balitorids, channids, mastacembelids, belonids and cobitids. Distribution pattern and abundance data showed that the species Tor tor, Tor putitora, Chaguninus chagunio, Barilius barila, Opsarius barna, Danio rerio, Lepidocephalichthys guntea, Parachiloglanis hodgarti and Amblyceps mangois were not common in the study area. The environmental variables such as depth, width, discharge and temperature showed effect upon species richness, abundance, distribution and diversity indices, which had lower values at upstream pre-urban sites than at downstream post-urban sites. A sharp decline in species richness, abundance and diversity indices at urban site (10 species) indicated urban influence.